The economic dividend of competitiveness - Fredrik Erixon; Oscar Guinea; Philipp Lamprecht; Elena Sisto; Erik Van der Marel (European Centre for International Political Economy (ECIPE), 2023)
In a world of technological and economic rivalry, the EU must devote increased attention to its competitiveness. Higher levels of competitiveness will help the EU build a more prosperous economy which will in turn produce innovation and resources to address the great challenges of our time. ECIPE published a study presenting a competitiveness compass with concrete policy recommendations that will improve EU's competitiveness. These policy recommendations, once implemented, will bring tangible benefits to the EU economy in the form of higher levels of trade and productivity. This report presents five scenarios in which the EU pursues competitiveness policies that lead to higher economic growth.
Keywords: 330; Internationaler Wettbewerb; EU-Staaten